1999
DOI: 10.1111/j.1600-0536.1999.tb06131.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological distinction between early allergic and irritant patch test reactions: follicular spongiosis may be characteristic of early allergic contact dermatitis

Abstract: Comparative light microscopic studies have revealed subtle differences between allergic and irritant reactions in the skin. In the search for specific differences, we focussed on the early inflammatory response. This pilot study was conducted to test the hypothesis that follicular spongiosis can differentiate between early allergic and irritant patch test reactions. 8 patients with known contact allergy to either colophony or quarternium-15 participated in the study. In each patient, allergic and irritant patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Follicular reactions of the poral type have been described after nickel contact, but whether these reactions are irritant or allergic is unknown . Nevertheless, follicular spongiosis may be observed in early allergic, but not irritant, reactions . A follicular reaction may also be a result of a low level of allergen exposure…”
Section: Diagnosing Nickel Allergymentioning
confidence: 99%
“…Follicular reactions of the poral type have been described after nickel contact, but whether these reactions are irritant or allergic is unknown . Nevertheless, follicular spongiosis may be observed in early allergic, but not irritant, reactions . A follicular reaction may also be a result of a low level of allergen exposure…”
Section: Diagnosing Nickel Allergymentioning
confidence: 99%
“…14 Furthermore, ACD produces a pattern of follicular spongiosis whereas ICD does not. 15 Differences in cytokine expression include the demonstration that ACD results in high levels of IL-10 in the elicitation phase whereas ICD does not, 16 and that the chemokines IP-10, Mig, and IP-9 are increased in ACD but not in ICD. 17 However, these methods require invasive, costly, and timeconsuming procedures and are not widely available for clinical application.…”
mentioning
confidence: 98%
“…These data prove that it may be difficult to interpret follicular reactions and make clinical judgements from them. Recently, it was shown that it is possible to make a distinction between early (6–8 hr after exposure) allergic and irritant patch test reactions as follicular spongiosis may be observed in allergic reactions (326).…”
mentioning
confidence: 99%